2017
DOI: 10.1111/dmcn.13576
|View full text |Cite
|
Sign up to set email alerts
|

Care maps for children with medical complexity

Abstract: Care maps were endorsed as a useful tool by families and providers. They help healthcare providers better understand parental priorities for care. Parents can create care maps to demonstrate the complex burden of care. They are a unique visual way to incorporate narrative medicine into practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 16 publications
2
31
0
Order By: Relevance
“…CMC typically have multiple chronic conditions, functional limitations, medical technology dependence (e.g., feeding tubes), and a complex network of service providers and caregivers critical to maintain day-to-day health. 6 Care network disruptions could generate outsized adverse consequences for CMC. As primary and specialty healthcare access is reduced, novel guidance for home health and medical equipment agencies is needed on in-home practices, including on conserving personal protective equipment and augmenting the home health workforce.…”
Section: Children With Medical Complexity (Cmc)mentioning
confidence: 99%
“…CMC typically have multiple chronic conditions, functional limitations, medical technology dependence (e.g., feeding tubes), and a complex network of service providers and caregivers critical to maintain day-to-day health. 6 Care network disruptions could generate outsized adverse consequences for CMC. As primary and specialty healthcare access is reduced, novel guidance for home health and medical equipment agencies is needed on in-home practices, including on conserving personal protective equipment and augmenting the home health workforce.…”
Section: Children With Medical Complexity (Cmc)mentioning
confidence: 99%
“…Care mapping is a useful tool for identifying resources, facilitating care coordination, and communicating a comprehensive snapshot of the youth and family needs and care priorities. 29 Care mapping fits well into the SMART framework for transition as it elucidates the multitude of social-ecological needs of youth with LGS and DS and highlights potential areas of intervention. 27 A social worker or nurse familiar with care mapping can help guide the family in developing their care map.…”
Section: The Transition Of Care Processmentioning
confidence: 89%
“…A similar process called person‐centered planning is used when developing life goals with individuals having intellectual and developmental disabilities. Care mapping as investigated by Adams et al came to prominence when Cristin Lind created an illustration to describe the persons and entities she worked with to manage her son's complex care. Ms. Lind quickly realized the power of ‘Gabe's Map’ and collaborated with Dr Richard Antonelli at Boston Children's Hospital to advocate and disseminate the care mapping process.…”
mentioning
confidence: 99%
“…The clinical research team that spearheaded the definition for children with medical complexity and demonstrated the usefulness of care planning has now addressed this gap in clinical knowledge. Adams et al describe the purpose and process for developing a care map and utilize a well‐designed qualitative investigation to present evidence for the clinical feasibility and usefulness of the process …”
mentioning
confidence: 99%
See 1 more Smart Citation